IM-UNITI: Three-year Efficacy, Safety, and Immunogenicity of Ustekinumab Treatment of Crohn's Disease. (3rd June 2019) - Hanauer, Stephen B; Sandborn, William J; Feagan, Brian G; Gasink, Christopher; Jacobstein, Douglas; Zou, Bin; Johanns, Jewel; Adedokun, Omoniyi J; Sands, Bruce E; Rutgeerts, Paul; de Villiers, Willem J S; Colombel, Jean-Frédéric; et al.
Abstract: Background and Aims: Following induction/maintenance treatment in the UNITI/IM-UNITI studies of ustekinumab for Crohn's disease, patients entered a long-term extension for up to 5 years from induction. Efficacy through 152 and safety through 156 weeks are reported. Methods: At IM-UNITI Week 44, 567 ustekinumab-treated patients entered the long-term extension and continued to receive blinded subcutaneous ustekinumab on their assigned dose interval, without any subsequent dose adjustment. Placebo-treated patients discontinued after study unblinding [after IM-UNITI Week 44 analyses]. Efficacy data in the long-term extension [LTE] were collected every 12 weeks [q12w] before unblinding and then at q12w/q8w dosing visits. Results: Through Week 156, 29.6% of ustekinumab-treated patients discontinued. In an intent-to-treat analysis of randomised patients from IM-UNITI Weeks 0–152, 38.0% of ustekinumab induction responders receiving the drug q12w and 43.0% q8w were in remission at Week 152. Among patients entering the long-term extension in their original randomised groups, 61.9% of q12w and 69.5% of q8w patients were in remission at Week 152. Across all ustekinumab-treated patients [randomised and non-randomised] entering the long-term extension, remission rates at Week 152 were 56.3% and 55.1% for q12w and q8w, respectively. Safety events [per 100 patient-years] were similar among all ustekinumab-treated patients entering the long-term extension and placebo [overall adverse events 389.70 vs 444.17; serious adverse events, 18.97 vs 19.54; serious infections, 4.21 vs 3.97]. Rates of antibodies to ustekinumab through Week 156 remained low, 4.6% in all randomised ustekinumab-treated patients; lowest among patients in the original randomised q8w group [2/82, 2.4%]. Conclusions: Continued treatment with subcutaneous ustekinumab maintained clinical response and remission through 3 years in a majority of patients who responded to induction therapy and was well-tolerated. ClinicalTrials.gov number NCT01369355.